Analisis Yuridis Pasal 112 dan Pasal 127 Undang-Undang Nomor 35 Tahun 2009 tentang Narkotika: Upaya Reformulasi untuk Menjamin Kepastian Hukum - Hariyawan, Agus Sukma; Purwani, Sagung Putri M.E. (Indonesian Journal Publisher, 2025)
This study aims to analyze the legal relationship between Article 112 and Article 127 of Law Number 35 of 2009 on Narcotics, focusing on formulating legal provisions that ensure legal certainty. The research adopts a normative legal method, employing approaches based on statutory regulations, conceptual analysis, and case studies. The findings reveal an overlap between the provisions of Article 112, which stipulates sanctions for drug distributors, and Article 127, which provides lighter sanctions, including rehabilitation, for drug abusers. The ambiguity in Article 112, particularly regarding narcotics usage, has led to prolonged debates and inconsistent application. This overlap has resulted in subjective interpretations by law enforcement officials, emphasizing the need for reformulated provisions grounded in the principles of lex certa and lex scripta. The study concludes that Article 112 should specifically address narcotics distributors, while Article 127 should focus on drug abusers, clarifying that the sanctions for abusers should prioritize rehabilitation measures. Such reformulation is essential to address legal uncertainty, reduce interpretative conflicts, and ensure proportional justice for narcotics offenders based on their roles and levels of culpability. These recommendations aim to foster a more consistent legal framework, enhancing the effectiveness of narcotics law enforcement while safeguarding the rights of justice seekers.